Gambaran Tingkat Pengetahuan Ibu Tentang Stimulasi Tumbuh Kembang Anak Prasekolah - Putri Nur aniffah; Elfrida Iriyani; Yulia Vanda Editia (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Data United International Children’s Emergency Fund (UNICEF) 2020stated that growth and development disorders in children under five were 27.5%. Fromthe results of a preliminary study on Friday 19 May 2023, TK ABA Pasekan Slemanhad 74 students, 37 boys and 37 girls. There are 5 students who experience motordisorders, one of whom is not fluent in reading, writing and drawing, the majority ofwhom are 6 years old and want to enter elementary school. Meanwhile, around 50%of children still have problems reading and writing. Result of survey The teacher'sintroduction at the ABA Pasekan Kindergarten stated that mothers did not know howto stimulate children according to their age. One mother even only followed her child'swishes so that the child rarely went to school. According to an interview with ABAPasekan Kindergarten Teachers, Early Growth and Development InterventionDetection Stimulation (SDIDTK) was carried out from the Community Health Center,but this year it has not been carried out.Purpose: Knowing the description of mothers' level of knowledge regarding themeaning, forms and principles of growth and development stimulation for preschoolchildren at the ABA Pasekan Kindergarten.Method: The research design used is a quantitative descriptive research design witha quantitative approachcross sectional. The samples taken were 74 mothers usingtotalsampling. The research was conducted in May-June 2023.Result: It shows that some respondents, namely 51 mothers (68.9%) have goodknowledge. Meanwhile, 23 mothers (31.1%) had insufficient knowledge. The resultsof the research stated that some respondents had good knowledge due to thecharacteristics of the respondents, most of whom had a high school/vocational highschool-university education of 62 (83.8%).Keywords: Growth and development, motor skills, knowledge